Impact of Odor from a Landfill Site on Surrounding Areas: A Case Study in Ho Chi Minh City, Vietnam: DOI: 10.32526/ennrj.18.4.2020.31 - Tran, Linh Hoang; Murayama, Takehiko; Enomoto, Chouzou; Nishikizawa, Shigeo (Environment and Natural Resources Journal, 2020)
Airborne pollutants and odor emissions generated from landfill operations can adversely affect human health and social well-being. Consequently, these pollutants and emissions must be controlled and regulated. The dispersion of odors in the areas surrounding landfills can create public complaints regarding air quality and can increase social tension. The purpose of this study is to explore the odor impact from a landfill on neighboring areas by measuring odor concentration and conducting a community survey. The research was conducted on Da Phuoc municipal solid waste management facility in Ho Chi Minh City, Vietnam. The results of our study indicate that odor concentration is proportional to distance from a landfill. By contrast, the annoyance level of residents differs between areas. This research is the first attempt to explore the odor impact from a landfill by measuring odor concentration in the Ho Chi Minh city of Vietnam. Our findings can help enhance environmental protection.